Modulation of Summer Squash Growth and Productivity Via Spiritual Blessings (Biofield) Energy Treatment (SBET) - Trivedi, Dahryn; Dattaram Kadam, Vivek; Rajendra Phutankar, Nikhil; Bapu Gaikwad, Tejas; Mondal, Sambhu; Jana, Snehasis (Journal of Farming, 2026)
Background The increasing demand for sustainable and eco-friendly agricultural practices has led to the exploration of non-traditional methods to enhance crop yield and resilience. Spiritual Blessings (Biofield) Energy Treatment (SBET), a form of consciousness-driven energy healing, is increasingly being investigated for its potential to modulate biological systems at the cellular and molecular levels without use of chemical additives Objective This study aimed to evaluate the impact of SBET on the growth characteristics and overall productivity of summer squash (Cucurbita pepo L.). Methods The study was conducted using a controlled experimental design, where seeds and plots were divided into two groups: control and treated. The treated group received a remote SBET by a recognized practitioner, while the control group remained untreated. Both groups were maintained under identical environmental conditions (soil, water). Parameters such as germination rate, plant height, leaf area index, and total fruit yield were monitored over a full growth cycle. Results Results showed that plant height, number of branches, and total number of leaves per plant were significantly improved by 35.14% (p ≤ 0.001), 41.64% (p = 0.011), and 49.01% (p = 0.029), respectively, in the treatment group compared to the control group. Additionally, fruit length and total fruit yield (tons per hectare) were significantly increased by 39.68% (p = 0.002) and 15.92%, respectively, in the treatment group compared to the control group. Conclusion Exposure of SBET significantly improved both vegetative and reproductive development, yielding substantial increases in plant height, branching, and leaf production.
Keywords: green zucchini; spiritual blessing; prayer; morphology; phenology; yield